Efficiency of seed extraction methods in the control of loss and low seed quality in egusi melon (Colocynthis citrullus L.) - P. E., Ogbonna; L. C., Odo (Global Journal of Food and Agribusiness Management, 2019)
This study determines the effect of methods of seed extraction on seed loss and viability on Egusi melon (Colocynthis citrullus L). Three methods of fruit breaking; vertical cut with knife, horizontal cut with knife and hitting with wooden club were tested to determine their effect on seed damage. Three covering materials; grass straw, black polyethylene sheet and no cover were also tested to determine their effect on the number of days to fruit fermentation and seed germination. The result showed that percentage seed loss resulting from vertical cutting with knife was 16% and was significantly higher than 3.4% seed loss arising from horizontal cut with knife and 0% from hitting with wooden club. It was also discovered that fruits covered with grass straw took 8.67 days to complete fruit fermentation while under black polyethylene cover it occurred at 12 days. Fruits that were left uncovered fermented at 9.33 days. Seed germination was also significantly affected by covering materials. Seed germination of 85.3, 80.0 and 30.0 were recorded on seeds obtained from fruits that were fermented with no cover, grass straw and black polyethylene cover respectively